A Supply-Side Evaluation of Coastal Tourism Diversification: The Case of Cyprus - Farmaki, Anna (My University, 2012)
Although several coastal resorts have attempted diversification of their "sea and sun" tourism products, the concept of tourism product diversification has received limited attention. As diversification has become a marketing trend for coastal destinations the degree of success of the strategy in increasing tourism revenue and repositioning destinations has varied. The purpose of this research study is to address this gap in literature and to offer insights on the success level of coastal mass tourism diversification. Qualitative research, in the form of interviews, was performed with the supply-sector of the Cyprus tourism industry in order to explore the attitudes of tourism professionals to a variety of issues related to diversification such as the context in which the strategy was adopted, its success degree and the factors affecting its success. The research findings support the economic data that reveal the failure of the diversification strategy of the Cyprus coastal tourism product. The research further discusses the factors that prohibited the successful implementation of diversification in Cyprus and the related implications. It concludes by identifying the success factors of diversification of other coastal destinations, which are used to provide a framework of success criteria for coastal tourism diversification.